The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1182/blood.v81.11.2925.bloodjournal81112925
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, immunological, and in vivo functional characterization of B-domain-deleted factor VIII

Abstract: Coagulation factor VIII (FVIII) is a cofactor in the intrinsic pathway of blood coagulation for which deficiency results in the bleeding disorder hemophilia A. FVIII contains a domain structure of A1-A2-B-A3- C1-C2 of which the B domain is dispensable for procoagulant activity in vitro. In this report, we compare the properties of B-domain-deleted FVIII (residues 760 through 1639, designated LA-VIII) to wildtype recombinant FVIII. In transfected Chinese hamster ovary (CHO) cells, LA- VIII was expressed at a 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Deficiency of FVIII results in bleeding disorder commonly known as hemophilia A. 9,31–33 We used a list of 27 peptides each 12 residue long selected against mAb Bo2C11 targeting the C 2 domain of FVIII. 31 Using the X-ray crystal structure of the C 2 domain of FVIII 34 (PDB id:1IQD), EpiSearch method predicted a potential epitope on the C 2 domain of FVIII that correspond to a patch centered at the residue R2220 with the highest score (0.937).…”
Section: Resultsmentioning
confidence: 99%
“…Deficiency of FVIII results in bleeding disorder commonly known as hemophilia A. 9,31–33 We used a list of 27 peptides each 12 residue long selected against mAb Bo2C11 targeting the C 2 domain of FVIII. 31 Using the X-ray crystal structure of the C 2 domain of FVIII 34 (PDB id:1IQD), EpiSearch method predicted a potential epitope on the C 2 domain of FVIII that correspond to a patch centered at the residue R2220 with the highest score (0.937).…”
Section: Resultsmentioning
confidence: 99%
“…The human B-domain deleted FVIII was chosen in this study, because the B-domain structure does not require procoagulant activity in contrast to full-length of human FVIII cDNA which contains a domain structure of A1-A2-B-A3-C1-C2. 16 The B-domain deleted hFVIII retains coagulant activity and is secreted from cultured cells more efficiently than with full length FVIII. Furthermore, it is less sensitive to degradation.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the open reading frame of FVIII is 7055 bp long and it has been much harder to express in viral vectors [ 140 ]. Different strategies have been applied to make the FVIII cDNA a bit shorter, and hence easier to introduce into different vectors, including using a B-domain deleted version of FVIII cDNA [ 141 , 142 ] as this domain does not appear to be essential for coagulation [ 14 , 143 – 145 ].…”
Section: Delivery Methodsmentioning
confidence: 99%
“…Indeed, studies performed in transgenic mice have demonstrated that these “minigene constructs” are very susceptible to being switched off by neighbouring chromatin [ 13 ]. On the other hand, there are cases where the cDNA is too big to be contained in one of these vector systems and some “nonessential” regions have to be eliminated [ 14 ].…”
Section: The Rationale Behind the Use Of Large Dna Molecules In Gementioning
confidence: 99%